Volume of the Thumb Carpometacarpal Joint - Lutsky, Kevin F.; Liss, Fred; Graham, Jack; Beredjiklian, Pedro K. (Journal of Wrist Surgery, 2020)
Background The volume of the carpometacarpal joint of the thumb (TCMC) and its capacity to accommodate fluid injection is unknown.Questions/Purpose The purpose of the present study is to assess the volume of the TCMC.Methods Forty-two thumbs undergoing surgical treatment for symptomatic TCMCJ osteoarthritis (OA) were evaluated. Prior to the start of the surgical procedure saline was injected into the TCMC until resistance was felt and no further saline could be injected. The maximum volume (MaxVol) of injectate was measured and recorded.Results Mean MaxVol among all patients was 0.9 cc (range: 0.2–3.0 cc). There were 15 patients with 1 cc or more injected, the rest were less than 1 cc. The mean MaxVol for Eaton 2 thumbs was 1.5 cc, for Eaton 3 thumbs 0.9 cc, and for Eaton 4 thumbs 0.7 cc, with negative correlation between Eaton stage and MaxVol.Conclusion TCMC has limited capacity for injected fluid.Level of Evidence This is a Level II, diagnostic study.
Keywords: carpometacarpal joint; thumb; volume; fluid injection